2015
DOI: 10.5901/mjss.2015.v6n6p201
|View full text |Cite
|
Sign up to set email alerts
|

Principles of Innovational Startup Selection for E-Platforms Placement

Abstract: This article shows the research results of startup companies' selection for their further placement on E-platforms for the purpose of attracting investments. The brief analysis of innovation tendency for small enterprises is given in the article. The authors drew up a conclusion that the level of innovation projects realization is not

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
1
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 0 publications
1
1
0
2
Order By: Relevance
“…2) transferring most of the powers of SMEs regulating from the federal to the local level. Note that this trend is observed in Russia (Morkovina, 2015).…”
Section: Introductionsupporting
confidence: 62%
“…2) transferring most of the powers of SMEs regulating from the federal to the local level. Note that this trend is observed in Russia (Morkovina, 2015).…”
Section: Introductionsupporting
confidence: 62%
“…In addition, studies have shown that when the amount of capital flowing into the market increases, venture capital firms are more willing to invest in early-stage companies instead of late-stage companies [7][8]. Enterprise innovation is one of the key characteristics of a start-up company [9][10].…”
Section: Discussionmentioning
confidence: 99%
“…Ada beberapa tahap dalam menelusuri start-up, yaitu persiapan, pemilihan perusahaan dan proyek inovasi dalam inkubasi (Morkovina et al, 2015). Kesuksesan inkubasi start-up terletak pada sumber daya manusia pendamping dan kurikulum pengajaran pada inkubator.…”
Section: Hasil Dan Diskusiunclassified